Decentralization of OPDs of Basic and Rural Healthcare Units of Punjab, Pakistan - Awais Gohar; Ejaz Qureshi; Farah Ahmad; Hasnain Javed; Warda Fatima; Nida Abdul Qadir (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Decentralization is associated with political administration and historical development, and varies according to region and implementation factors. In the 1980s, the IMF (International Monetary Fund) and World Bank demonstrated that corruption and bad administration in society are due to centralization policies which concentrate authority and power in the hands of the elite upper class. This criticism was an initial point to start the period of structural decentralization adjustment. Decentralization is a substantial process for equal distribution of healthcare service delivery in the community. The outdoor patient department (OPD) is one of the most important parts of any health care unit to diagnose and treat patients who do not require overnight care or stay in hospitals. The main purpose of this research was to analyze the effect of decentralization and improvements in health services for OPD by analyzing the number of patients in Primary Healthcare Centers (Basic Health Unit (BHU) and Rural Health Centers (RHCs)) in Punjab before and after de-centralization. Non-probability convenient and simple random sampling technique was employed, and patients visiting PHCs (primary healthcare centers) OPD were included in the study population. OPD patients of rural and basic healthcare units were categorized into three pairs OPD 1, 2 and 3, and the means and other statistical parameters were calculated using SPSS. The average mean of all groups of OPD patients of RHCs were 119441.1111, 192536.5185 and 153487.1358, respectively. The average mean of all groups of BHU was 94818.5062, 109331.7160, and 124231.0123, respectively. The results showed that the number of patients in the OPD increased after decentralization due to more health facilities.